Defining Avoidable and Unavoidable Complications in Spine Surgery: A Survey-based Study of Spine Fellowship Directors. Issue 11 (1st June 2016) - Khaleel, Mohammed A.; Bono, Christopher M.; White, Andrew P.; Wood, Kirkham B.; Harris, Mitchel B.; Wagner, Katiri; Zurakowski, David; McGuire, Kevin J.
Abstract : Study Design: A cross-sectional survey of orthopedic spine surgery fellowship directors in the United States. Objective: The aim of this study was to investigate whether consensus exists with respect to spine-related adverse events and certain hospital-acquired conditions (HACs) or "never events." Summary of Background Data: As part of a broad effort to improve health care outcomes, providers are no longer reimbursed for HACs, which are deemed avoidable. Although some HACs are unquestionably preventable with proper quality control measures, research suggests that even scrupulous adherence to evidence-based guidelines cannot eliminate others. Methods: Surveys were distributed via email and post. Participants rated 27 HACs and selected spine-specific events on an ordinal scale. Interobserver reliability was assessed among all 46 spine directors (respondents) using the intraclass correlation coefficient (ICC), based on a two-way random effects model, assuming that the participants were a representative population sample of spine surgeons. Multivariable linear regression analyses were performed on each of the 27 complications to identify potential demographic factors that could be associated with variation among respondents in their ratings of "avoidable" to "unavoidable." Results: Forty-six fellowship directors responded, of whom 98% were orthopedic spine surgeons. The majority (80.4%) of respondents had greater than 10 years' experience as a spine surgeon, and 66.7% had an annual surgical volume >201 cases. The multivariable linear regression analyses found that demographic factors were not predictive of the directors' ratings. The complications thought to be completely avoidable (median scores 1) included "Incompatible blood, " "Retained foreign object, " and "Wrong level surgery." The HAC considered least avoidable was "Site infection with risk factors" (median score 8). Among 17 spine-specific complications, "L4-L5 disc re-herniation within 3 months" (median score 9) was considered least avoidable. Conclusion: This survey suggests that orthopedic spine surgeons consider most "never events" neither avoidable nor unavoidable. There is strong consensus only about the HACs resulting from obvious medical error. Level of Evidence: 4 Abstract : Supplemental Digital Content is available in the text